Maternal care factors associated with peripartum and postpartum obstetric complications according to the demographic and family health survey in 2021 - Calapuja-Larico, Jeniffer Susy (2024)
Objectives: Determine the association between maternal care factors and peripartum and postpartum obstetric complications. Material and methods: Quantitative, analytical, retrospective and cross-sectional study, based on data from ENDES 2022.  Results: A sample of 6 158 mothers was analyzed, 22.2 % of whom had obstetric complications. The most frequent were postpartum fever (12%) and peripartum bleeding (9.9%). The maternal care factors associated with increased peripartum complications were; family violence (PRa=1.6; 95%CI1.16-2.20; p=0.004), DM2 (PRa=4.11; 95%CI1.85-9.10; p=0.001) and receive ferrotherapy (PRa=9.76; 95%CI:1.88-50.64; p=0.007), on the other hand, prenatal care provided by qualified personnel (PRa=0.29; 95% CI 0.13 - 0.65; p=0.003) will decrease these probabilities. On the other hand, HTN (PRa=2.3; 95% CI: 1.10-4.82; p=0.027), T2DM(PRa=4),Anemia(PRa=2.11),emotional violence (PRa=2.22) increase the possibility of complications while Hb control (PRa= 0.52; 95%CI: 0.31-2.76; p=0.014), early postpartum care (PRa=0.19) by qualified personnel (PRa=0.66) decreases the prevalence of postpartum complications.  Conclusions:  Maternal care factors significantly associated with postpartum and peripartum obstetric complications were characteristic of NPC, intervention and preventive-promotional actions, as well as risk factors such as hypertension, T2DM, anemia, and family violence.